2020
DOI: 10.1002/jcsm.12522
|View full text |Cite
|
Sign up to set email alerts
|

p300 and cAMP response element‐binding protein‐binding protein in skeletal muscle homeostasis, contractile function, and survival

Abstract: Background Reversible ε-amino acetylation of lysine residues regulates transcription as well as metabolic flux; however, roles for specific lysine acetyltransferases in skeletal muscle physiology and function are unknown. In this study, we investigated the role of the related acetyltransferases p300 and cAMP response element-binding protein-binding protein (CBP) in skeletal muscle transcriptional homeostasis and physiology in adult mice. Methods Mice with skeletal muscle-specific and inducible knockout of p300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 72 publications
6
28
0
Order By: Relevance
“…Our experiments in astrocytes, analysis of KAT3 peaks in different tissues and previous observations in other cell types demonstrating that the combined loss of CBP and p300 causes impaired cell-type-specific transcription [30][31][32][33] , all support this view. Further supporting this model, a very recent study in mice with skeletal muscle-specific and inducible combined ablation of p300 and CBP revealed that the two proteins are also jointly required for the control and maintenance of contractile function and transcriptional homeostasis in skeletal muscle 60 . What may differ between cell types is the specific set of TFs that recruit the KAT3 proteins to cell-type-specific loci.…”
Section: Discussionmentioning
confidence: 65%
“…Our experiments in astrocytes, analysis of KAT3 peaks in different tissues and previous observations in other cell types demonstrating that the combined loss of CBP and p300 causes impaired cell-type-specific transcription [30][31][32][33] , all support this view. Further supporting this model, a very recent study in mice with skeletal muscle-specific and inducible combined ablation of p300 and CBP revealed that the two proteins are also jointly required for the control and maintenance of contractile function and transcriptional homeostasis in skeletal muscle 60 . What may differ between cell types is the specific set of TFs that recruit the KAT3 proteins to cell-type-specific loci.…”
Section: Discussionmentioning
confidence: 65%
“…We attributed this lack of effect to the well-documented compensatory actions of p300 and CBP that occur when only p300 or CBP is present ( 25 , 26 ). Thus, we interbred these individual knockout models to generate a p300 and CBP skeletal muscle–specific, tamoxifen-inducible, double-knockout mouse (referred to as PCKO), which we previously described ( 27 ). Because PCKO mice die 6–7 days after initiating tamoxifen treatment ( 27 ), in this study all experiments in PCKO mice and wild-type (WT) littermates were conducted at day 1 (D1), 3 (D3), or 5 (D5) after starting tamoxifen dosing.…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, we studied a separate cohort of PCKO mice with measures being made on D5 after initiating tamoxifen dosing; D5 was chosen as there was a robust abrogation of insulin-stimulated glucose uptake by skeletal muscle in PCKO mice at this timepoint. The CBP KO/p300 HZ and p300 KO/CBP HZ lines have been described previously (27).…”
Section: A Single Allele Of P300 or Cbp Rescues Glucose Intolerance And The Loss Of Skeletal Muscle Insulinstimulated Glucose Uptake Seenmentioning
confidence: 99%
See 2 more Smart Citations